Optimalisasi kapasitas energi angin dan matahari dengan konfigurasi mikrogrid berdasarkan karakteristik beban - Dhanis Woro Fittrin Selo Nur Giyatno; Lukman Bagus Subekti; Adlan Bagus Pradana; Indriana Nurmawati; Indra Wibowo (Jurnal Teknosains, 2021)
Diploma III Electrical Technology Study Program is a institutional vocational education institutional in Department of Electrical Engineering and Informatics that aims to produce graduate who are ready to work in operation and maintenance of power system. Since phenomena of scarcity of fossil fuels, study program meet the 2 major problems, namely the limitations of electrical energy for practical lab work and increased job skills on the electrical energy conversion of electrical energy from renewable energy. The purpose of this research is to optimalize capacity of solar and wind energy contained in the environment of the laboratory on the microgrid configuration, namely PV-Wind turbine-Battery. Software HOMER is used to simulate microgrid configuration with AC-DC load, AC load, and DC load. The results show indicate that microgrid PV-Wind turbine-Battery is more economically to meet the need AC-DC load than the others.